2013
DOI: 10.7763/ijesd.2013.v4.382
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tangerine Oil against Aspergillus niger Identified from Raw and Boron Treated Rubberwood

Abstract: Abstract-The antifungal efficacy of tangerine oil at various concentrations (10-200 μL/mL) were tested in agar medium and on rubberwood surface against Aspergillus niger indentified from raw and boron treated rubberwood. Various dilutions were made in methanol and vegetable oil was used as a control. Components of the tangerine oil were determined by means of gas chromatography-mass spectrometry (GC-MS) analysis. Minimum inhibitory concentrations (MICs) of tangerine oil against A. niger identified from raw and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…of its colony growth's coverage to the total surface area of the wood samples. The value was then converted into a scoring system according to Jantamas et al (2013) as presented in Table 1.…”
Section: Isolation Of Stain Fungi For Significant Growthmentioning
confidence: 99%
“…of its colony growth's coverage to the total surface area of the wood samples. The value was then converted into a scoring system according to Jantamas et al (2013) as presented in Table 1.…”
Section: Isolation Of Stain Fungi For Significant Growthmentioning
confidence: 99%
“…The percentage growth of isolate to the surface area of the wood test samples was represented by score. Score 0 indicated that there is no growth of isolate on wood test samples and scores 5 indicated the heavy stain fungi growth, which was 0: no growth, 1: 20% growth of stain fungi on wood test samples, 2: 40%, 3: 60%, 4: 80% and 5: 100% (Jantamas et al 2013).…”
Section: Isolation and Selection Of Fungimentioning
confidence: 99%
“…Essential oils are natural complex compounds as a result of secondary metabolites from aromatic plants, which play a role in plant protection against pathogens [6]. The main constituents of citronella oil are Citronellal (27.5%), geraniol (20.4%), citronellol (13.4%) [7]. Lemongrass oil is used as an antispasmodic, rubefacient, stimulant, insect repellent, carminative, and diaphoretic [8].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the essential oils inhibited the germination of urediniospores H. Vastatrix [11], had antifungal activity against Penicillium [12], the effectiveness of clove oil (Syzygium aromaticum) against Venturia inaequalisstrains [13], eugenol oil nanoemulsion protects cotton seeds from Fusarium wilt [14], inhibits the germination of Aspergillus flavus spores in rubberwood [7].…”
Section: Introductionmentioning
confidence: 99%